2021
DOI: 10.1002/jum.15814
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Findings to Predict Risk of Recurrence in Pediatric Intussusception After Air Enema Reduction

Abstract: Objectives Intussusception is one of the most common abdominal emergencies in early children. Intussusception recurs in 8–20% of children after successful nonoperative reduction. The aim of this study was to explore the ultrasound findings to predict risk of recurrence in pediatric intussusception after air enema reduction. Methods A total of 336 intussusception children were followed up for 1 year after received successful air enema reduction. They were divided into the recurrent group and the non‐recurrent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(81 reference statements)
1
4
0
Order By: Relevance
“…Our analysis also identified mesenteric lymph node enlargement as a predictor of in-hospital recurrence of intestinal intussusception (OR = 1.90). This result agrees with the study of Zhang et al, who found that enlarged abdominal lymph nodes were related to recurrence of intussusception [ 20 ]. Adhikari et al also observed that the incidence of lymph node enlargement was numerically higher in the recurrence group than in the non-recurrence group (61.5% vs. 47.7%), although the difference was not statistically significant [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our analysis also identified mesenteric lymph node enlargement as a predictor of in-hospital recurrence of intestinal intussusception (OR = 1.90). This result agrees with the study of Zhang et al, who found that enlarged abdominal lymph nodes were related to recurrence of intussusception [ 20 ]. Adhikari et al also observed that the incidence of lymph node enlargement was numerically higher in the recurrence group than in the non-recurrence group (61.5% vs. 47.7%), although the difference was not statistically significant [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, Guo et al found that symptom duration ≤ 12 h and mass located in the right abdomen were independent predictors of recurrent intussusception [ 13 ], whereas the factors identified by Xie et al included duration of symptoms ≥ 48 h and mass located in the left abdomen [ 16 ]. Furthermore, Zhang et al demonstrated that mass diameter > 2.55 cm and enlarged abdominal lymph nodes were related to recurrence of intussusception [ 20 ], whereas Vo et al did not identify any radiologic features that were associated with early recurrence, although the risk of recurrence was higher in females and patients with fever [ 17 ]. A recent meta-analysis by Ye et al identified only fever, absence of vomiting and PLPs as factors associated with a higher risk of recurrence of intestinal intussusception [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Duc et al ( 21 ) found that surgical intussusception had a significantly smaller diameter than non-surgical intussusception. Zhang et al ( 22 ) reported that intussusception recurrence was prone with greater mass diameter. Consistent with previous studies, logistic regression analysis used in this study showed that long-axis diameter was identified as an independent predictor of surgical intervention for intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors such as age, light weight (9, 25), temperature >37.8°C (9,22) and location of mass (9) were identified as independent predictors for non-surgical intussusception reduction failure in previous studies. However, in the present study, these factors did not show strong association with surgical intervention after hydrostatic reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is extremely important and necessary to develop a simple and effective way of predicting recurrent intussusception. There have been several studies exploring the risk factors of recurrent intussusception such as age, duration of symptoms and absence of vomiting, [10][11][12] but they are still incomplete. Intestines play an important role in regulating systemic immune inflammation as the body's largest lymphoid organ.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%